Evaluation Of Character Education Policy(Case Study Of Bandung Masagi Program At SMP Negeri36 Bandung City) - Sudrajat, Tatang; Hanny Rahayu; Lenny Kristianti; Artanty Fauziyah; Puteri Regina (Universitas 17 Agustus 1945, 2025)
National character is very necessary for the organization of the state and national development. Character education is an important part of state and government policies. The issuance of several state, government and local government regulations regarding character education is a form of public policy, which must be comprehensively evaluated. The study aims to evaluate the substance and implementation of character education policies in the form of the Bandung Masagi Program at SMP Negeri 36, Bandung City. The study uses a qualitative approach with normative legal methods and case study evaluation. State policies in the form of Law Number 20 of 2003 and Law Number 17 of 2007, Presidential Regulation Number 87 of 2017, Minister of Education and Culture Regulation Number 23 of 2015, Minister of Education and Culture Regulation Number 20 of 2018, Bandung City Regulation Number 2 of 2018, and Bandung Mayor Regulation Number 004 of 2019 show serious attention to national character, including the character of students. In general, the hierarchical structural relationship between one regulation set at the government level and the government level below it. Schools run the Bandung Masagi program according to their capabilities and resources. Teachers and education personnel carry out their duties with demands to continue to improve innovation and creativity. There are several policy substances that need to be refined.